The impact of heating and drying on protease activities of ruminant milk before and after in vitro infant digestion - Leite JAS; Montoya CA; Loveday SM; Mullaney JA; Loo TS; McNabb WC; Roy NC (Elsevier Ltd, 2023)
This study investigated the effect of heating (63°C/30 min or 75°C/15 s) and drying (spray-drying or freeze-drying) on plasmin, cathepsin D, and elastase activities in bovine, ovine, and caprine milk, compared to non-dried raw milk counterparts. Protease activities and protein hydrolysis were assessed before and after in vitro infant digestion with or without gastric and pancreatic enzymes. At 75°C/15 s, plasmin activity in caprine and ovine milk decreased (69-75%, p<0.05), while cathepsin D activity in spray-dried bovine milk heated increased (2.8-fold, p<0.05). Plasmin and cathepsin D activities increased (<1.2-fold, p<0.05) after in vitro digestion with pancreatin, regardless of milk species. Endogenous milk enzymes hydrolyzed more proteins than gastric enzymes during gastric digestion and contributed to small intestinal digestion. In summary, milk proteases remained active after processing with effects dependent on the species of milk, and they contributed to in vitro protein hydrolysis in the stomach and small intestine.
Keywords: Digestion; Drying; Heating; Proteases; Protein hydrolysis; Ruminant milk; Humans; Infant; Animals; Sheep; Goats; Milk; Ruminants; Milk Proteins; Proteolysis; Digestion; Hot Temperature; Cathepsin D